2018
DOI: 10.1038/s41598-018-30541-3
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles-induced cytotoxicity in triple negative breast cancer involves different epigenetic alterations depending upon the surface charge

Abstract: Gold nanoparticles (AuNPs) are used enormously in different cancers but very little is known regarding their molecular mechanism and surface charge role in the process of cell death. Here, we elucidate the molecular mechanism by which differentially charged AuNPs induce cytotoxicity in triple negative breast cancer (TNBC) cells. Cytotoxicity assay revealed that both negatively charged (citrate-capped) and positively charged (cysteamine-capped) AuNPs induced cell-death in a dose-dependent manner. We provide fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 43 publications
8
66
0
Order By: Relevance
“…These results showed that AuNPs-loaded nanoemulsion (group VI) could inhibit the proliferation of the invasive breast cancer cells and did not moderate the non-invasive cancer cells as well as the non-transformed breast cells. Similar results were reported by other researchers, who observed the inhibition of the breast cancer cells treated with the AuNPs [62,63]. However, in our study it was observed that the proliferation activity of the human cancer invasive cells was selectively inhibited Table 2).…”
Section: Colorimetric Mtt Assaysupporting
confidence: 92%
“…These results showed that AuNPs-loaded nanoemulsion (group VI) could inhibit the proliferation of the invasive breast cancer cells and did not moderate the non-invasive cancer cells as well as the non-transformed breast cells. Similar results were reported by other researchers, who observed the inhibition of the breast cancer cells treated with the AuNPs [62,63]. However, in our study it was observed that the proliferation activity of the human cancer invasive cells was selectively inhibited Table 2).…”
Section: Colorimetric Mtt Assaysupporting
confidence: 92%
“…They attributed the cytotoxicity effects of GNPs to the generation of oxidative stress in a dose-dependent manner in cancer cell lines; cysteamine-capped GNPs showed more oxidative stress in comparison to citrate-capped GNPs, while no oxidative stress was generated by GNPs in normal cells. 35 Furthermore, the cytotoxicity of citrate-capped GNPs (20 nm) on the MRC-5 human fetal lung fibroblast cell line at different concentrations of studied by Li et al, where, they did not observe a significant difference in the percentage of cell death between the treatment and control groups after 24, 48, and 72 hours incubation, which confirms our founding on selective cytotoxicity of GNPs in cancer cells. 36 Different mechanisms have been considered for GNPs' cytotoxicity; GNPs can induce diverse types of cell death through reactive oxygen species (ROS) production and mitochondrial function disturbance.…”
Section: Discussionsupporting
confidence: 87%
“…Studies have shown that GNPs' toxicity depends on their size, shape, surface charge, stabilising agent, etc. [18,19,41]. In this context, we showed previously that USP-generated GNPs made of pure gold do not affect the viability of cells in sizes 20-100 nm [29,36].…”
Section: Discussionmentioning
confidence: 81%